X-chromosome-linked inhibitor of apoptosis as a key factor for chemoresistance in clear cell carcinoma of the ovary - Miyamoto, M (Nature Publishing Group, 2014)
BACKGROUND: X-chromosome-linked inhibitor of apoptosis (XIAP) is one of the anti-apoptotic proteins leading to chemoresistance in several cancers. The aim of this study is to evaluate the impact of XIAP expression upon ovarian clear cell carcinoma (CCC) that has a platinum-resistant phenotype. METHODS: Tissue microarrays made from 90 CCC patients were analysed for immunohistochemical expression levels of XIAP, c-Met, p-Akt and Bcl-XL. In addition, CCC cell lines were evaluated whether XIAP silencing could modulate sensitivity to platinum agent in vitro. RESULTS: High XIAP expression was observed in 30 (33%) of 90 CCC cases, and was associated with c-Met (<0.01) and Bcl-XL (<0.01) expression. Cases with high XIAP expression had lower response rate to primary platinum-based chemotherapy (10% vs 65%, P=0.02). In stages II–IV tumours, high XIAP expression was related with worse progression-free survival (PFS, P=0.02). Furthermore, high XIAP expression was identified as an independent worse prognostic factor for PFS and overall survival. Finally, downregulation of XIAP using XIAP-specific small interfering RNA increased sensitivity to cisplatin in human cancer cells derived from CCC. CONCLUSIONS: X-chromosome-linked inhibitor of apoptosis expression was correlated with chemoresistance of primary chemotherapy, and identified as a prognostic marker for CCC. X-chromosome-linked inhibitor of apoptosis could be a candidate for new therapeutic target in CCC.